Women's Transitions from Welfare to Paid Work and Education: Learning to Navigate the Systems - Cynthia Lee Andruske (Adult Education Research Conference, 1999)
The purpose of this research is to highlight women's strategies for navigating their transitions from welfare to paid work and education.